Aspirations, self-prospects and level of optimism of children in conflict with the law - Concepcion, Janette G. (2007)
The prevalence of child offenders is constantly increasing. This study is a descriptive and normative study which aimed to depict the aspirations, prospects and optimism of the children in conflict with the law in five facets: education, employment, family, community relations, and self improvement. The research was conducted in two major detention centers in Metro Manila. The researcher-designed instruments were administered to 40 child-respondents. Results revealed that children in conflict with the law aspire to work to uplift their financial status. The aspirations, self-prospects and optimism of the children showed significant correlations, indicating that high optimism elicits better prospects (plans) to fulfill their aspirations. With right opportunities and guidance, the children in conflict with the law will succeed in life.
"March 2007."
Thesis (M.A. Special Education)--University of the Philippines Diliman.
Keywords: Juvenile delinquents -- Philippines -- Manila Metropolitan Area -- Psychology; Juvenile delinquency -- Philippines -- Manila Metropolitan Area